Immune profiling of plasma-derived extracellular vesicles identifies Parkinson disease - Elena Vacchi; Jacopo Burrello; Dario Di Silvestre; Alessio Burrello; Sara Bolis; Pierluigi Mauri; Giuseppe Vassalli; Carlo W. Cereda; Cinthia Farina; Lucio Barile; Alain Kaelin‐Lang; Giorgia Melli (2020)
Objective To develop a diagnostic model based on plasma-derived extracellular vesicle (EV) subpopulations in Parkinson disease (PD) and atypical parkinsonism (AP), we applied an innovative flow cytometric multiplex bead-based platform. Methods Plasma-derived EVs were isolated from PD, matched healthy controls, multiple system atrophy (MSA), and AP with tauopathies (AP-Tau). The expression levels of 37 EV surface markers were measured by flow cytometry and correlated with clinical scales. A diagnostic model based on EV surface markers expression was built via supervised machine learning algorithms and validated in an external cohort. Results Distinctive pools of EV surface markers related to inflammatory and immune cells stratified patients according to the clinical diagnosis. PD and MSA displayed a greater pool of overexpressed immune markers, suggesting a different immune dysregulation in PD and MSA vs AP-Tau. The receiver operating characteristic curve analysis of a compound EV marker showed optimal diagnostic performance for PD (area under the curve [AUC] 0.908; sensitivity 96.3%, specificity 78.9%) and MSA (AUC 0.974; sensitivity 100%, specificity 94.7%) and good accuracy for AP-Tau (AUC 0.718; sensitivity 77.8%, specificity 89.5%). A diagnostic model based on EV marker expression correctly classified 88.9% of patients with reliable diagnostic performance after internal and external validations. Conclusions Immune profiling of plasmatic EVs represents a crucial step toward the identification of biomarkers of disease for PD and AP.